Bilateral Spontaneous Pneumothorax: A Rare Clinical Presentation of Pulmonary Metastases of Synovialosarcoma - Belliraj, Layla; Hejjar, Chaymae; Ouadnouni, Yassine; Smahi, Mohamed (Advances in Thoracic Diseases, 2020)
Bilateral spontaneous pneumothorax is a very rare condition that occurs mainly in patients with underlying lung disease. We present the case of spontaneous bilateral pneumothorax in a young patient treated for a synovial sarcoma of the right foot.